A study design to assess the safety and efficacy of on-pump versus off-pump coronary bypass grafting: the ROOBY trial - Novitzky, Dimitri; Shroyer, A Laurie; Collins, Joseph F; McDonald, Gerald O; Lucke, John; Hattler, Brack; Kozora, Elizabeth; Bradham, Douglas D; Baltz, Janet; Grover, Frederick L (Clinical trials (London, England), 2007)
Background Since the late 1960s, coronary artery bypass graft (CABG-only) procedures were traditionally performed using a heart-lung machine on an arrested heart (on-pump). Over the past decade, an increasing number CABG-only procedures were performed on a beating heart (off-pump). Advocates of the off-pump approach expect to reduce many of the adverse side effects related to using the heart-lung machine, while advocates for the on-pump procedure raise concerns related to graft patency rates and long-term event-free survival for the off-pump technique. Purpose The U.S. Department of Veteran Affairs (VA) Cooperative Studies Program funded a randomized, multicenter clinical trial comparing the clinical and resourcerelated outcomes following on-pump versus off-pump techniques for veterans undergoing a non-emergent CABG-only procedure. The planning committee was faced with several critically important challenges to assure feasibility of study costs and required sample size; generalizability to non-VA surgical practices; and comparability of clinically meaningful results. These challenges are discussed. Methods This study is a prospective, randomized, multicenter, single blinded (patient) clinical trial that compares on-pump and off-pump techniques for veterans requiring non-emergent CABG-only procedures. There will be 2200 patients randomized at 17 VA Medical Centers when the five-year recruitment period ends on 15 April 2007. There are two primary objectives: a short-term objective to assess the immediate impact of the two techniques on 30-day mortality/morbidity and a long-term objective to assess one-year mortality/morbidity. Major secondary outcomes are one-year graft patency rates and change in neuropsychological assessments from baseline to one year. All patients are assessed at 30 days post-surgery or discharge from the hospital, whichever is latest, and at one-year post-surgery. Results During planning, several key issues had to be decided. These included 1) choosing primary objectives: a short-term (30-day) and a long-term (one-year) objective were chosen; 2) choosing primary outcome measures: composite measures were selected to ensure sufficient end-points; 3) standardization of surgical techniques: minimal standardization required but guidelines and continuing discussions on both techniques provided; 4) establishing criteria for surgeons and residents for participation: surgeons required to have completed 20 off-pump procedures prior to doing study procedures and residents, in presence of study surgeon, capable of doing either procedure; 5) identifying metrics of cognitive dysfunction sensitive to treatment: a neuropshychologist hired who centrally monitors cognitive functioning testing; and 6) blinding participants of surgical procedure: attempt to blind participants. Limitations Areas of concern are whether all surgeons sufficiently experienced on the off-pump procedure, should residents have been allowed to do study surgeries, should techniques have been standardized more and were the best neurocognitive tests selected. Conclusion The study design presented allows for a balanced and fair assessment of the on-pump and off-pump CABG procedures across a diversity of clinical outcomes and resource use metrics. Its results have the potential to influence clinical cardiac surgical practice in the future.